1992
DOI: 10.1002/mrd.1080330310
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization, development, and implantation after exposure of mature mouse oocytes to visible light

Abstract: Mature mouse oocytes were exposed prior to in vitro fertilization to visible light during 1, 2, or 4 hr at an intensity of 4,000 lux. Compared to controls cultured under identical conditions but protected from light, exposed eggs did not show any significant modification of cleavage speed and rate. After transfer of blastocysts obtained in vitro in uteri of pseudopregnant females, the implantation rate and the proportion of normal fetuses were not found to be different in relation to preliminary light exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Our results showed that mouse 2-cell embryos may not tolerate exposure to visible light longer than 45 min in either simple (HTF) or complex (MEM-α) culture media. Exposure of mouse oocytes to 4,000 lx illumination had no adverse effect on the rate of implantation following IVF and embryo transfer [13]. Similar to mouse oocytes and in contrast to mouse 2-cell embryos (our results), rabbit day 1 embryos are less sensitive to visible light and they may tolerate 8 h exposure to visible light.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our results showed that mouse 2-cell embryos may not tolerate exposure to visible light longer than 45 min in either simple (HTF) or complex (MEM-α) culture media. Exposure of mouse oocytes to 4,000 lx illumination had no adverse effect on the rate of implantation following IVF and embryo transfer [13]. Similar to mouse oocytes and in contrast to mouse 2-cell embryos (our results), rabbit day 1 embryos are less sensitive to visible light and they may tolerate 8 h exposure to visible light.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, development of hamster 1-cell embryos has also been impaired following exposure to visible light in a timedependant manner [8]. In contrast, mouse oocytes exposed to 4,000 lx visible light for 1 to 4 h had both normal fertilization and speed of cleavage [13]. A recent study by Takenaka (2007), in which B6D2F1 mouse zygotes were exposed to light from different sources and transferred into surrogate mothers, has shown very short exposure to sunlight and 15 min exposure to cool white fluorescent light reduced the rate of live term fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength, power, and exposure time of a biological specimen to light determines the level of damage to that sample. As a result, previous studies on oocyte viability and embryo development after exposure to light have resulted in different conclusions, with some studies reporting no effect (Kruger & Stander, 1985;Sauer et al, 1991;Barlow et al, 1992) and other studies reporting a variety of impediments, including inhibition of cleavage and cell death, to oocyte and embryo development (Daniel, 1964;Hirao & Yanagimachi, 1978;Fischer et al, 1988;Hegele-Hartung et al, 1988Nakayama et al, 1994;Squirrell et al, 1999). To properly evaluate the potential toxic effects of OQM, we first measured the wavelength and power at the specimen level.…”
Section: Discussionmentioning
confidence: 99%
“…Retardation in cleavage of mouse and rabbit embryos by light has also been reported (12)(13)(14). It is important to realize that under natural conditions, mammalian oocytes and embryos are never exposed to sunlight or strong artificial light.…”
mentioning
confidence: 99%